Peranan Dakwah Mr. Sjafruddin Prawiranegara dalam Menyelamatkan Republik - Sriyanto Sriyanto (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2019)
Mr. Sjafruddin Prawiranegara is a unique figure in thinking and preaching. He was a great preacher and given contributions for republic . Another learning, da'i should not be prosecutor and judge. Sjafruddin role, as a da’i the president often erased from history books. Based on this, Study entitled the role Sjafruddin Prawiranegara Dakwah in saving Republic was carried out. This research very important because to re-read role of Mr. Sjafruddin Dakwah, da'i warrior who has saved existence and sustainability of Republic as part of his faith. This research is limited to role of his dakwah, biography, concept of struggle and relevance his dakwah. This research is qualitative as a library with interpretative approach. The results of research indicate that his dakwah based on strong Islamic worldview. Digest Dakwah covering faith and reason is basis of preaching.